Do Rater Personality Traits Moderate the Relationship Between Intelligence and Rating Accuracy in Interviews? - Bassier, Laeeqa (School of Management Studies, 2022)
Research on judgment accuracy in human resource management shows that various rater characteristics predict accuracy, but emerging findings suggest that these individual differences may interact with one another (rather than being direct effects). The present study aimed to add to this area of research by determining how rater personality traits may moderate the relationship between GMA and rating accuracy. Secondary data collected in a prior study of police managers undergoing a seven-week managerial training course in South Africa (N =146) were analysed. The findings supported that selected rater personality traits may moderate the relationship between intelligence and rating accuracy. For example, rater intelligence was a better predictor of accuracy when the judge was more agreeable. Intellectance and conscientiousness were found to have no significant moderating effect on the relationship between intelligence and rating accuracy. Only three out of the Big Five Personality traits were examined in this research study. Importantly, the study contributed to theory by expanding the Good Judge model (De Kock et al., 2020), analysing how individual differences in the ability and trait domains may potentially interact to influence accuracy. In addition to enhancing our understanding of how rater personality constructs may affect accuracy, the study discusses important implications for practices, such as rater training and selection.